种连续配筋混凝土路面膨胀剂掺量确定方法 (2018)
本发明公开了种连续配筋混凝土路面膨胀剂掺量确定方法，通过制备不同膨胀剂的试件，再绘制膨胀剂掺量与裂缝宽度、应力的关系曲线，最后根据关系曲线确定最佳掺量，本发明确定膨胀剂掺量的方法简单，且定量确定了连续配筋混凝土路面膨胀剂掺量值，根据最佳掺量添加膨胀剂制成的连续配筋混凝土可以有效避免了由于膨胀剂掺量值过少而引起连续配筋混凝土路面裂缝宽度较大以及膨胀剂掺量值过大而造成的连续配筋混凝土路面拱起破坏。 The invention discloses a determination method for the mixing amount of an expanding agent added into a continuous reinforced concrete pavement. The method comprises the following steps: preparing test pieces with different amounts of the expanding agent; then drafting a relation curve of the mixing amounts of the expanding agent, crack widths and stress; and determining an optimal mixing amount according to the relation curve. The method is simple and quantitatively determines the mixing amount of the expanding agent to be added into a continuous reinforced concrete pavement; and the continuous reinforced concrete pavement with an optimal mixing amount of the expanding agent can prevent too large crack width of the continuous reinforced concrete pavement due to a too small mixing amount of the expanding agent and